2019
DOI: 10.2106/jbjs.18.00458
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Joint Laxity in Orthopaedic Patients

Abstract: ➤ Careful history and examination may reveal a constellation of musculoskeletal conditions associated with generalized joint laxity, including shoulder instability, posterolateral rotatory instability of the elbow, wrist ganglia, thumb base pathology, hip labral pathology, and patellar and ankle instability.➤ Subtle but highly suggestive findings associated with generalized joint laxity may be recognized on radiographs or magnetic resonance imaging that can impact the clinician’s decision-making.➤ Increasing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Patients in the first group (LPD group) were required to have had at least 2 episodes of nontraumatic patellar dislocation, with physical and radiological examinations confirming the diagnoses, to meet the inclusion criteria. Patients with a history of operation or trauma, generalized joint laxity (defined as a Beighton score of ≥4 points), 35 passive hyperextension greater than 10° (bilateral testing), and patellofemoral osteoarthritis were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the first group (LPD group) were required to have had at least 2 episodes of nontraumatic patellar dislocation, with physical and radiological examinations confirming the diagnoses, to meet the inclusion criteria. Patients with a history of operation or trauma, generalized joint laxity (defined as a Beighton score of ≥4 points), 35 passive hyperextension greater than 10° (bilateral testing), and patellofemoral osteoarthritis were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…However, it must be noted that a joint may be hypermobile yet stable, and the differentiating factor between hypermobility and instability is the presence of symptoms (9). When a majority of an individual's synovial joints are capable of excessive motion, the patient is diagnosed with generalized joint hypermobility (GJH) (10), which is a hallmark of hereditary disorders of connective tissue.…”
Section: Definitionsmentioning
confidence: 99%
“…In a cadaveric study, hip capsular laxity caused increased joint rotations, femoral head translations, and abnormal movement of the femoral head, leading to microinstability (2). This excess motion of the femur relative the acetabulum can lead to damage to the labrum, cartilage, and capsular structures over time (10). Additionally, Devitt et al demonstrated that in patients undergoing hip arthroscopy for the treatment of FAIS, the presence of GJH was predictive of hip capsular thickness, with those with GJH having a thinner hip capsule (<10 mm) than those without (64).…”
Section: Natural History and Instability Of Hip Hypermobilitymentioning
confidence: 99%
“…In 1973, the Beighton score was identified as an appealing method of diagnosing GJH because it utilized 5 basic clinical tests and had a simple 9-point scoring system. 1,8,27 These early studies suggested that GJH predisposed patients to recurrent dislocation, early arthritis, effusions, ligamentous injury, and premature osteoarthritis. 7…”
mentioning
confidence: 99%
“…In 1973, the Beighton score was identified as an appealing method of diagnosing GJH because it utilized 5 basic clinical tests and had a simple 9-point scoring system. 1,8,27 These early studies suggested that GJH predisposed patients to recurrent dislocation, early arthritis, effusions, ligamentous injury, and premature osteoarthritis. 7 More recently, the anterior cruciate ligament (ACL) literature has brought attention to GJH, which is now a well-recognized risk factor for poor outcomes after ACL reconstruction and has been implicated as a potential risk factor for ACL injury.…”
mentioning
confidence: 99%